Sistematización de la experiencia sobre la actualización del manual de clasificación de puestos en la Dirección de Talento Humano, perteneciente a la Gerencia Administrativa Financiera de la Empresa Pública Metropolitana de Movilidad y Obras Públicas, en el periodo septiembre 2016 agosto 2017 - Lema Ordóñez, David Rafael (2018)
The following systematization explain the process of a project accomplished in the Empresa Pública Metropolitana de Movilidad y Obras Públicas, in the Human Talent Management concern to update the Job positions classification manual in the Human Talent Management of the Empresa Pública Metropolitana de Movilidad y Obras Públicas in the period September 2016 to August 2017. The Empresa Pública Metropolitana de Movilidad y Obras Públicas is responsible for the administration and execution of mobility and public works in the city of Quito, they are in charge of maintenance, construction, road signs, preservation and care of public spaces (parks, squares). The reason to develop and execute this project designed to update the Job positions classification manual in the in the human talent management obeys the fact that it has not be update more than 3 years ago, likewise the interest for the present is due to the elimination of 2 degrees in the occupational scale, it means review all the minims requirements for each job position. By the exposed before, was consider as a vital need to start as a pilot plan updating the Job positions classification manual in the Human Talent Management, then will be retort with Management and Directions of all the Company.